MENGUKUR KINERJA DISTRIBUSI BATU-BARA OLEH UKM DARI TAMBANG HINGGA PELABUHAN - Hendy Tannady; Dino Caesaron (Universitas Bunda Mulia, 2017)
At present, a logistic services for coal manufacturer company is very important. However, often happen that production process goes faster than logistic services in delivery mining product from the mining area to the port. DEA (Data Envelopment Analysis) is expected will produce a parameter that can use to justified whether the perfomance of the job effective and efficient. This research will focus on evaluating the performance of four Small Medium Enterprise which operate their business in delivering the coal mining, from the mining area to the harbour. Element of the input is the number of the truck, loading and unloading manpower, and the number of truck which is return in one hour. Element of the output is the number of coal mining at the port. After data is analyzed by WinQSB, the conclusion is obtained that SME C and D operate better In terms of efficiency and optimization of than SME A and B. Keywords: Logistic, Coal, Data Envelopment Analysis